(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Mexico, the postgraduate educational system has been in greater demand according to the needs of the professional and work context, for this, Higher Education Institutions offer postgraduate specialization, master’s and doctorate degrees. In Mexico, based on the National Association of Universities and Institutions of Higher Education (ANUIES), it is reported that for the 2019-2020 school year there was an enrollment of 384,614 students enrolled in various educational establishments. What reinforces the increase of scientists and professionals in various fields, however, at the moment that an applicant becomes a registered student, the criteria for entry, permanence, follow-up, graduation and terminal efficiency, makes an educational program a success, due to the fact that, when the number of students who entered the postgraduate degree, In this sense, this document presents 6 postgraduate educational programs in the area of Social Sciences and Humanities based on a comparison of the indicators of graduation and terminal efficiency of 2 master’s degrees and 2 doctorates belonging to the National Quality Postgraduate Program of the National Council of Science and Technology with 2 master’s degrees that do not belong to the aforementioned National Program.